Exploring sustainable manufacturing: A bibliometric analysis of low-carbon technology integration - Nur Sofia Nabila, Alimin; Norhana, Mohd Aripin; Suhaidah, Hussain; Salina, Daud; Lee, Khai Loon; Bathaei, Ahmad; Wan Nuraisyah Balqis, Ahmad Bustamam (EDP Sciences, 2025)
This study provides a bibliometric analysis of low-carbon technology integration within the manufacturing industry, drawing from 313 publications indexed in the Scopus database to examine scholarly trends and future directions. Low-carbon technologies, encompassing innovations in green manufacturing, energy storage, digital transformation, and policy strategies, are important for sustainable industrial practices. Utilising bibliographic coupling and co-occurrence analysis techniques, this research indicates the evolution of literature from foundational studies to emerging themes. In bibliographic coupling analysis, clusters such as “Regulation and Policy of Low-Carbon Technology,” “Behavioural Shifts Toward Low-Carbon Practices,” and “Business Performance of Green Technology Innovation” highlight the influential factors shaping past and present research. Co-occurrence analysis reveals future-oriented clusters like “Innovation of Low-Carbon Technologies,” “Climate and Environmental Impact,” and “Policies for Sustainable Manufacturing,” reflecting a growing emphasis on digital innovation, hybrid energy solutions, and strategic policy development. Theoretically, this study bridges gaps by offering an integrated understanding of technological, financial, and behavioural drivers in sustainable manufacturing. Practically, it provides valuable insights for industry practitioners and policymakers aiming to enhance energy efficiency, promote green innovation, and accelerate the transition to a low-carbon economy.